ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PEMOHON PASPOR DI KANTOR IMIGRASI KELAS I TPI NGURAH RAI - Juan Bryan Sebayang; Lukia Zuraida; Teguh Hadisukarno (Politeknik Pariwisata Bali, 2025)
This study analyzes the effect of service quality on the satisfaction of passport applicants at the Ngurah Rai Class I Immigration Office. The research was motivated by a high number of public complaints and information requests, as well as relatively low public ratings on Google Reviews compared to other immigration offices in Bali. The study adopts the Service Quality (SERVQUAL) theory developed by Parasuraman, Zeithaml, and Berry, which includes five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. A descriptive and inferential quantitative approach was employed, involving 140 respondents aged 17 and above who had applied for passports. The sampling technique used was purposive sampling. Data were collected through questionnaires and analyzed using descriptive statistics and simple linear regression with SPSS version 29. The findings indicate that all service quality dimensions were rated very good, with average scores above 3.3. Regression analysis shows that service quality has a positive and significant effect on applicant satisfaction. Respondents expressed satisfaction with facilities, response speed, assurance, and staff empathy. However, improvements are needed in aspects such as the cleanliness of waiting areas and restrooms, clarity of application procedures, administrative support, and fairness in service delivery. These results highlight the need for continuous service evaluation and improvement in public service institutions.